The chemical composition analysis of dwarf saltwort (Salicornia bigelovii Torr.) and its preservative effects on snakehead fish fillets. Issue 4 (16th March 2022) - Wang, Dujun; Wang, Yue; Dong, Guangsong; Shang, Yueling; Lyu, Yongmei; Li, Fengwei; Zhang, Chunyin; Yu, Xiaohong
Abstract: In this study, the nutritional component and chemical constituents of Salicornia bigelovii Torr. were investigated, as well as their preservative effects on aquatic products. LC–MS of S. bigelovii extracts detected 34 compounds, eight flavonoids were identified based on standard substance. Camellianin A and noreugenin were identified for the first time in S. bigelovii . Furthermore, the S. bigelovii could reduce the fish fillet loss rate and inhibit the growth of microorganisms in aquatic products that impact cooking loss rate, pH, total volatile basic nitrogen, total viable count, and it also could reduce the damage of myofibrillar proteins texture changes. Finally, the S. bigelovii had a strong inhibitory effect on the dominant spoilage bacteria Pseudomonas in snakehead fish was demonstrated, and significantly prolong the preservation time of fish fillet till the 12 days. Overall, this study provides a basis for the selection of suitable methods for the preservation and processing of aquatic products. Novelty impact statement: The Salicornia bigelovii was found a strong inhibitory effect on the bacteria Pseudomonas in snakehead fish, and it can significantly prolong the preservation time of fish fillet, which were expected to be used as the selection of suitable methods for the preservation and processing of aquatic products.